Navigasi Robot Quadruped Menggunakan Kamera - Muhammad Notonugroho; Sujono Sujono (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
In a 4-legged robot designer in a simulation following a line that has been made in such a way using a camera and avoiding furniture. But in this simulation arena add a red line as a robot reference to follow the line and the arena has obstacles turning right, turning left and crossroad. In this arena furniture will also be added as a robot challenge to avoid it. This robot consists of 12 servo motors of each foot using 3 servo, 4 ultrasonic sensors, CMUcam5, line sensors, Arduino Mega 2560. CMUcam is used to read the midpoint of the red line that will be the path of the robot while to read furniture that is by using an ultrsonic sensor . When the robot has found the midpoint of the coordinate, with the X-axis of the line being in the middle of the robot, if the X-coordinate is greater than 180 then the robot's position is on the line and if the X-coordinate is less than 180 then the robot's position is on the line. The speed of the robot once rotating around the track is 0.017 m / s with a length of 5.72 meters. The results obtained are robots can navigate using the camera properly and succeed in avoiding furniture.